Ultrasound diagnostics in ophthalmology (standardized echography) : Part 1: principles and diseases of the eyeball - Hasenfratz, G.; Mardin, C. (Ophthalmologe, 2014)
Ultrasound diagnostics has been one of the most important additional diagnostic non-invasive techniques in ophthalmology for many decades and is essential for many intraocular and orbital diseases. When echographic investigations and analysis of the echograms obtained are correctly carried out, ultrasound diagnostics demonstrates a high degree of specificity and sensitivity.
EVALuna2:21187